Nurse Staffing Norm in Iran Hospitals: What Features Should be Included for Success? - Tabatabaee, Seyed Saeed (Int J Prev Med, 2017)
BACKGROUND: Designing and implementing a model for estimation and distribution of required nurse is one of strategies to prevent unequal distribution of nurses within and between hospitals. The purpose of this research was to determine required features for hospital nursing staff estimation model. METHODS: We conducted a qualitative study using a Colaizzi analysis approach. We used semi-structure and in-depth interviews by purposive, quota, and snowball sampling of 32 participants (10 informed experts in area of policy making in human resources in Ministry of Health, 10 decisions making in employment and distribution of human resources in treatment and administrative chancellors of medical universities, and 12 process owners in hospitals). The data were analyzed using ATLAS.ti software version 6.0.15. RESULTS: The ten following sub-themes emerged from data analysis: Skill mix and task shifting, work measurement, legal support, stakeholder involvement in designing a model, considering the ward activity, considering type and extent of care patients required, model development by experts predominate in nursing process, considering the nurses availability, considering the capabilities and professional merits of nurses, fitness with social, cultural, and belief of people. The main themes were occupation analysis, planning and policy making, real workload, acceptability, nurses’ efficiency, and being a native. CONCLUSIONS: Given that standardization of nursing staff estimation is announced as one of the challenges in reaching Iran's 20-year vision plan. Hence, design and implementation of a nursing staff estimation model in regard to identified features could be part of priorities in Ministry of Health in Iran.